Update on clinical, imaging, and therapeutic aspects of kissing molars: A systematic review (Research, Society and Development, 2021)
Introduction: The Kissing Molar (KM) is defined by two or more lower posterior teeth in contact with the occlusal surfaces and the roots in opposite directions. Purpose: This study aimed to review epidemiological, clinical, and imaging aspects related to Kissing Molars. Methods: A two-phase systematic review registered in the PROSPERO platform was performed. Search strategies were developed for specific databases (PubMed, Scopus, Web of Science, Scielo, and LILACS), including the gray literature (Open Grey and Google Scholar). The CARE guideline was followed to evaluate methodological aspects, and the Joanna Briggs Institute instrument (MAStARI) assessed the risk of bias. Statistical analysis considered a 5% level of significance. Results: The initial search strategy resulted in 564 articles. From this total, 21 studies (case reports and case series) meet the eligibility criteria. The main aspects associated with KMs (n=32) were laterality difference between males and females (p=0.028), report of mental retardation (p=0.023), the involvement of second (p=0.036) and third (p